Effects of early reinforcement to academically low-performing physiology students at Davao Medical School Foundation - Maruya, Mila O.; Erlyn A. Sana PhD (2006)
Davao Medical School Foundation (DMSF) has to admit students who could be considered academically challenged or underachievers in order to sustain its operations at the same time help these students improve their academic performance in order for the school to achieve its goal of generating competent and committed graduates who will serve the communities of Davao and the rest of Mindanao. This study was conducted in response to the need to understand the effect of early intervention in the performance of academically low performing students and to describe the effect of early intervention on their attitudes towards learning. Twenty-two physiology medical students of the DMSF who failed in their preliminary examination were subjected to an early intervention program. The preliminary examination was used as pretest. Posttests given were quizzes 1-4, midterm and final examinations. The same group was subjected to a pretest and posttest to compare their attitude toward learning prior to and after the intervention through the use of attitudinal rating scale. Comparison of the actual ratings of students in the pretest and posttest showed improvement in students' performance. Students' performance has increased individually and as a group. Except for a few who did not perform well in quizzes 1 and 2 and final examination but showed improvement in the midterm period. The rest however showed a marked increase. This may be attributed to a series of interventions done after the preliminary examinations and until the final term. The result of t-test in comparing means of 2 groups was -3.089, p=0.006. This value is lower than the set value of 0.05 so that null hypothesis 1(H01) was rejected. The result of the Analysis of Variance (ANOVA) on the other hand, revealed that except for quiz 2, performance differed significantly compared to the preliminary examination. The Wilcoxon signed ranks test on the comparison of pre and post attitudinal scores of students towards learning during classes revealed the result of z=-3.018, p=0.003. The same test was used to determine the level of confidence of students in participating to the activities in the classroom. The test yielded a value of z=-2.745, p=0.006. Since the obtained p value was less than 0.05, the decision was to reject null hypothesis 2 ((H02). This study concludes that there is a significant difference in the performance of academically low performing students before and after early intervention and that there is also a significant effect of early intervention on their attitudes toward learning and their level of confidence when attending classes. This study recommends an institutionalization of an early intervention program especially for those low performing students admitted by the school. This also recommends that teachers must be given seminars and trainings in teaching strategies. Lastly, prompt feedback and giving reinforcement to students should be a matter of policy by the school to instill in the minds of the teachers that giving reinforcement or early feedback to students is part of the integral role of teachers
Thesis (Master in Health Professions Education)--University of the Philippines Manila
Panel Members: Erlyn A. Sana PhD, Chair/Adviser; Melflor A. Atienza MD MHPEd, Reader/Critic; Nemuel S. Fajutagana MD MHPEd, Member; Jose Alvin P. Mojica MD MHPEd, Member.
Keywords: Davao Medical School Foundation; Reinforcement (Psychology); Underachievers -- Education